‘Bring Back our Innocence’. Protecting Children from Commercial Sexual Exploitation: A Case Study of Three African Countries - Mavunga, Rufaro Audrey (Southern African Public Law, 2021)
The focus of this article is on the commercial sexual exploitation of children with a particular focus on the use of children for the purposes of prostitution and pornography in South Africa, Zimbabwe and Uganda. The article examines the international prohibition of child prostitution and pornography and analyses the extent to which these three countries have implemented the relevant international instruments in their national legal order. The research reveals that South Africa has enacted estimable legislation that prohibits the use of children for the purposes of prostitution and pornography, whereas Zimbabwe and Uganda’s legislation warrants some refinement. In addition, research identifies some of the challenges these countries are facing in implementing the respective legislative frameworks and, to that effect, the article author seeks to offer recommendations for overcoming such difficulties. The extent to which the three countries have incorporated international laws prohibiting child prostitution into their national legislation is analysed.